2010
DOI: 10.1128/aem.00477-10
|View full text |Cite
|
Sign up to set email alerts
|

AidH, an Alpha/Beta-Hydrolase Fold Family Member from an Ochrobactrum sp. Strain, Is a Novel N -Acylhomoserine Lactonase

Abstract: N-acylhomoserine lactones (AHLs) are signaling molecules in many quorum-sensing (QS) systems that regulate interactions between various pathogenic bacteria and their hosts. Quorum quenching by the enzymatic inactivation of AHLs holds great promise in preventing and treating infections, and several such enzymes have been reported. In this study, we report the characterization of a novel AHL-degrading protein from the soil bacterium Ochrobactrum sp. strain T63. This protein, termed AidH, shares no similarity wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 58 publications
1
74
1
1
Order By: Relevance
“…Despite their differences in DNA sequence and metal ion dependence ( Table 2), all of these enzymes were confirmed to function as lactonases following biochemical analysis of reaction products. Additionally, in vitro and in vivo studies have confirmed the overall value of these lactonases in quorum quenching and disease prevention against E. carotovora (62,68,71,72), akin to what was originally shown with AiiA.…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 87%
See 1 more Smart Citation
“…Despite their differences in DNA sequence and metal ion dependence ( Table 2), all of these enzymes were confirmed to function as lactonases following biochemical analysis of reaction products. Additionally, in vitro and in vivo studies have confirmed the overall value of these lactonases in quorum quenching and disease prevention against E. carotovora (62,68,71,72), akin to what was originally shown with AiiA.…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 87%
“…Metagenomic analyses faciliated the discovery of QlcA, BipB01, BipB04, BipB05, and BipB07 (68,74,75), and screens for AHL-degrading bacteria led to the identification of QsdA of Rhodococcus erythropolis strain W2 (70), AiiM of Microbacterium testaceum (71), AidH of Ochrobactrium sp. strain T63 (72), and QsdH of Pseudoalteromonas byunsanensis strain 1A01261 (73). Despite their differences in DNA sequence and metal ion dependence ( Table 2), all of these enzymes were confirmed to function as lactonases following biochemical analysis of reaction products.…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 99%
“…(AidH) and GsP being respectively dependent on Mn 2þ and Co 2þ for their lactonase activity. 26,27) More interesting is that the sequence similarity was high between GsP and GKL, even despite the distinct difference of metal effect, for which reason is not currently clear. 23) It should be noted that there is a difference in metal dependence between the GKL and AHL lactonases from G. caldoxylosilyticus YS-8, despite their similar substrate specificity and thermostability.…”
Section: Discussionmentioning
confidence: 99%
“…N-(3-oxododecanoyl)-L-homoserine (3-oxo-C12-HS), the lactonolysis product of OdDHL was prepared by incubating OdDHL in 200 μl DMSO (25 mM) mixed 300 μl of 1 M NaOH for 6 h at 37℃. The pH of the mixture was adjusted to 6.0 with H3PO4 and then the lactonolysis product was extracted three times with ethyl acetate (Mei et al, 2010). After evaporating the solvent under nitrogen flow to dryness, the residue was reconstituted in 500 μl of a methanol:water (1:1) and used as a standard lactonolysis product of OdDHL.…”
Section: Identification Of Qq Mechanism Of Strain Ro1s-5mentioning
confidence: 99%
“…on biofilm formation. To our knowledge, the only available reports about biofilm study with respect to AHL lactonase were: eradication of preformed biofilm (24 h-old) of PAO1 by an exposure to AiiA lactonase for 6 h at 37℃ (Kiran et al, 2011); reduction in biofilm formation by P. fluorescens strain 2P24 (pR8C-1) harboring aidH gene (Mei et al, 2010). In contrast to lactonase, inhibition of biofilm by AHL acylase has been extensively studied: acylase I-mediated inhibition of the biofilm formation by Aeromonas hydrophila and Pseudomonas putida (23-73%) and biofilms on RO membrane (20-24%) (Paul et al, 2009); acylase from Bacillus pumilus on the biofilm formation by PAO1 (20-87%) and S. marcescens (~ 61%) (Nithya et al, 2010); application of immobilized acylase in membrane bioreactors for biofouling control (Yeon et al, 2009; Cheong et al, 2013) and nanofiltration membrane (Kim et al, 2011).…”
mentioning
confidence: 99%